2014
DOI: 10.1103/physrevb.89.085422
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the transport properties of graphene films grown by CVD on SiC(0001): Effect ofin situhydrogenation and annealing

Abstract: The structural, optical, and transport properties of graphene grown by chemical vapor deposition (CVD) of propane under hydrogen on the Si face of SiC substrates have been investigated. We show that little changes in temperature during the growth can trigger the passivation of the SiC surface by hydrogen. Depending on the growth condition, hole or electron doping can be achieved, down to a few 10 11 cm −2. When the growth temperature is high (T ≈ 1500-1550 • C), we obtain electron-doped graphene monolayers lyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 36 publications
1
33
0
Order By: Relevance
“…S2). This could stem from both disorder-induced Landau level broadening (such an effect was also seen in graphene with similar mobility 32 ) and a finite thickness (side surface) effect 33 . At even higher temperature (>50 K), the bulk conduction starts to become significant and possibly suppress the QH states.…”
Section: Also Of Interest Inmentioning
confidence: 89%
“…S2). This could stem from both disorder-induced Landau level broadening (such an effect was also seen in graphene with similar mobility 32 ) and a finite thickness (side surface) effect 33 . At even higher temperature (>50 K), the bulk conduction starts to become significant and possibly suppress the QH states.…”
Section: Also Of Interest Inmentioning
confidence: 89%
“…(The supplementary material describes the dual alternating contact AFM technique 19 which contrasts the graphene from the surrounding SiO 2 . 24 ) The labeled wrinkle in Fig. 2(b) has a height of 3-12 nm which varies along its length.…”
mentioning
confidence: 97%
“…The most widely studied among the carbon sources is propane [114,121,124,126,[128][129][130][131][132][133][134][135][136][137]. There is only a few works devoted to ethene [125], toluene [127] and xylene [127] as carbon sources for graphene growth on silicon carbide.…”
Section: Growth Of Graphene On Sic Using External Sourcesmentioning
confidence: 99%
“…14). Up to this moment we considered only the literature reports devoted to propane-argon assisted growth, but there is also some interesting experimental data on CVD growth of graphene by using hydrogen as a carrier gas [114,126,129,131,132,136]. Michon et al [114,126,129] demonstrated the possibility of direct growth of graphene on 6H-SiC (0001) and 3C-SiC/Si substrates.…”
Section: Growth Of Graphene On Sic Using External Sourcesmentioning
confidence: 99%